Creating a national crime fiction through allegory translation: from Sherlock Holmes, the western detective to Relentless Avni, the turkish Sherlock Holmes - Altintas, Ozge; Karadag, Ayse Banu (SPRINGER, 2022)
We aim to examine Ebussureyya Sami's Relentless Avni, the Turkish Sherlock Holmes, the first Turkish crime fiction series in the Turkish literary system published in the late Ottoman Era, with a focus on allegory translation in crime fiction. Despite being considered as original in the Turkish literary system, the series under investigation raises the issue of whether it is original due to its similarities to western crime novels. Studies on crime fiction translation show that the genre is an important tool for creating national allegories which can be transformed into other allegories through translation. We argue that the series, albeit having been considered original in the Turkish literary system, constitutes an example of allegory translation produced through creative mediation due to the absence of an established crime fiction tradition in the Turkish literature at the time. The comparative analysis of the series and their western counterparts reveals that Ebussureyya Sami, the author-translator, transformed a Western-oriented allegory into a new national allegory for the readers to create a culture repertoire with a specific emphasis on Turkishness in line with the National Literature Movement and nationalist modernization in the Turkish target culture and the protagonist Relentless Avni, the Turkish Sherlock Holmes functioned as a contributor to culture planning by providing a role model of a nationalist modern Turkish citizen.
Keywords: Crime fiction; National allegory; Allegory translation; Creative mediation; Literature